2017
DOI: 10.4103/asl.asl_231_16
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of standardized extract of Passiflora incarnata flower in parkinson's and alzheimer's disease

Abstract: Background:Oxidative stress plays an important role in the pathogenesis of neurodegenerative diseases such as Alzheimer’s and Parkinson’s disease. Flavonoids exert their antioxidant effects by neutralizing all types of oxidizing radicals including the superoxide and hydroxyl radicals. Passiflora incarnata Linn. (Passifloraceae) is an important plant used in Ayurveda for the treatment of various disorders of the CNS and is a rich source of flavonoids.Aim:In the present study, we investigated the antioxidant, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 17 publications
0
9
0
2
Order By: Relevance
“…47 Passiflora incarnata Protects against oxidative damage Antioxidant activity. 48 Ginkgo biloba Neuroprotective in treatment of PD Restoration of olfactory loss. 49…”
Section: Discussionmentioning
confidence: 99%
“…47 Passiflora incarnata Protects against oxidative damage Antioxidant activity. 48 Ginkgo biloba Neuroprotective in treatment of PD Restoration of olfactory loss. 49…”
Section: Discussionmentioning
confidence: 99%
“…Some antioxidants rich natural extracts are believed to be neuroprotective, and therefore may have cognitive benefits in aging and neurodegenerative diseases (Rabadiya et al, 2012). For example, Ingale and Kasture (2017) found that the flower butanol extract improved PD by improving antioxidant capacity.…”
Section: Discussionmentioning
confidence: 99%
“…A cell culture study on twenty different South African medicinal PP-rich plants against AD reported the effectiveness of Xysmalobium undulatum, Cussonia paniculata, and Schotia brachypetala in decreasing the production of Aβ in comparison to other investigated extracts (Thakur et al, 2019). Moreover, based on the dietary intervention animal study of Ingale and Kasture (Ingale and Kasture, 2017), PP rich extract of purple passionflower could enhance cognitive function. Animal model studies, Capparis spinose, Caesalpinia crista, Iris germanica, and Paeonia suffruticosa could attenuate inflammation and Aβ aggregation through their polyphenolic contents, and make positive changes in cognition and memory (Costa et al, 2016;Gu et al, 2016;Borhani et al, 2017).…”
Section: Polyphenols and Their Anti-alzheimer's Disease Potentialmentioning
confidence: 99%